Volatiles from the Aerial Parts of East Mediterranean Clary Sage: Phytotoxic Activity. Issue 5 (3rd July 2016) - Bozok, Fuat; Ulukanli, Zeynep
Abstract: Aerial parts of Salvia sclarea L. were collected from natural populations of the outskirts of Çamliyayla Plateau (Turkey). The essential oil was isolated with Clevenger type apparatus and analyzed with GC and GC-MS. A total of 17 constituents were identified in the essential oil, which accounts for 94.4% of the total essential oil. The yield of the distillation was 0.3% (v/w). S. sclarea L. had the abundance of L-linalool (48.85%), linalyl acetate (16.67%), α-terpineol (6.06%), geraniol (4.38%), geranyl acetate (4.34%), (+)-aromadendrene (2.60%) and neryl acetate (2.15%). In the phytotoxicity assay, the essential oil showed significant dose dependent toxic potential on Lactuca sativa L., Lepidium sativum L. and Portulaca oleracea L. At the highest concentration, I) the seed germination was inhibited in P. oleracea L. (50%), in L. sativa L. (94%) and in L. sativum L. (100%); II) Inhibition of radicle and plumule length was 100% on the L. sativum L., 96.0% on L. sativa L. and 81.0% on P. oleracea L.; III) Fresh and dry weight showed reductions as follows; 84% and 88% in L. sativa L., 56% and 52% in P. oleracea L. . The present study concluded that S. sclarea L. is a rich source of terpenoid constituents and might be used as a bio-originated pesticide in nature.